Pushing for partnership: physician engagement and resistance in primary care renewal. Issue 2 (7th February 2019) - Kreindler, Sara A.; Struthers, Ashley; Metge, Colleen J.; Charette, Catherine; Harlos, Karen; Beaudin, Paul; Bapuji, Sunita B.; Botting, Ingrid; Francois, Jose
Abstract : Purpose: Healthcare policymakers and managers struggle to engage private physicians, who tend to view themselves as independent of the system, in new models of primary care. The purpose of this paper is to examine this issue through a social identity lens. Design/methodology/approach: Through in-depth interviews with 33 decision-makers and 31 fee-for-service family physicians, supplemented by document review and participant observation, the authors studied a Canadian province's early efforts to engage physicians in primary care renewal initiatives. Findings: Recognizing that the existing physician–system relationship was generally distant, decision-makers invested effort in relationship-building. However, decision-makers' rhetoric, as well as the design of their flagship initiative, evinced an attempt to proceed directly from interpersonal relationship-building to the establishment of formal intergroup partnership, with no intervening phase of supporting physicians' group identity and empowering them to assume equal partnership. The invitation to partnership did not resonate with most physicians: many viewed it as an inauthentic offer from an out-group ("bureaucrats") with discordant values; others interpreted partnership as a mere transactional exchange. Such perceptions posed barriers to physician participation in renewal activities. Practical implications: The pursuit of a premature degree of intergroup closeness can be counterproductive, heightening physician resistance. Originality/value: This study revealed that even a relatively subtle misalignment between a particular social identity management strategy and its intergroup context can have highly problematic ramifications. Findings advance the literature on social identity management and may facilitate the development of more effective engagement strategies.